Comparative Analysis of the Efficiency of Sharia and Conventional Life Insurance Industries in Indonesia - Jannara Dewaji; Khusnudin (Indonesian Journal of Business Analytics, 2025)
This study compares the efficiency of sharia and conventional life insurance in Indonesia using data envelopment analysis (DEA). Annual financial data from 24 sharia life insurance companies and 17 conventional life insurance companies for the period 2019–2023 were analyzed using the CRS, VRS, and SE approaches using MAX DEA 8 and Microsoft Excel. The results showed that based on the CRS and SE methods, 14 sharia life insurance companies and 6 conventional life insurance companies were efficient for five consecutive years. Meanwhile, based on the VRS method, there were 15 sharia life insurance companies and 9 conventional life insurance companies that were efficient in the same period. The main factors causing inefficiency are liabilities and operational expenses. This study emphasizes the importance of efficiency analysis in the life insurance industry to improve sustainability, support economic growth, and community welfare.